'It Was COVID-19': Keir Nuttall on life as a songwriter in the pandemic. Issue Volume 21:Number 1(2021)Special Issue:Part 1 (28th August 2021) - Carfoot, Gavin
Abstract : In this article I interview musician and songwriter Keir Nuttall about his experiences during the COVID-19 pandemic. Nuttall reflects on a number of key professional and personal issues that have affected his work and everyday life, starting with a discussion of his parody song 'It Was COVID-19', based on the song 'I Was Only 19' by Redgum. Nuttall discusses the role that the song played in coming to terms with the pandemic, and the reaction from the song's original writer John Schumann. Nuttall reflects on how cancelled performances and opportunities have impacted his life as a creative professional, including cancelled tours and the postponed Broadway development of Muriel's Wedding: The Musical, the musical that he wrote with his wife and creative partner Kate Miller-Heidke. Finally, Nuttall discusses how the lockdown in Melbourne and enforced periods of interstate quarantine have affected his creativity, his family life, the impacts on the broader music industry, and some of the rewarding personal and musical experiences that have also arisen at this time.